2002
DOI: 10.1017/s0021859602002666
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diversification of a rice–wheat cropping system on crop productivity and soil fertility

Abstract: SU MMARYField experiments were conducted at the Crop Research Centre of Govind Ballabh Pant University of Agriculture and Technology, Pantnagar during 1996/97 and 1997/98. Each experiment comprised 10 crop sequences : (a) wheat-rice, (b) chickpea-rice, (c) lentil-rice, (d) pea-rice, (e) wheat-mungbean green manure-rice, (f ) wheat-Sesbania green manure-rice, (g) wheat-fodder-rice, (h) chickpeafodder-rice, (i) lentil-fodder-rice and ( j) pea-fodder-rice, in a randomized block design with four replications. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 5 publications
(7 reference statements)
1
19
0
Order By: Relevance
“…In an intensive RWS, nutrient removal often exceeds replenishment through fertilizers [12][13][14][15][16]. LTEs continuing under diverse agro-ecologies in India underlined that neither the fertilizers nor the organic sources in isolation can achieve sustainable production.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an intensive RWS, nutrient removal often exceeds replenishment through fertilizers [12][13][14][15][16]. LTEs continuing under diverse agro-ecologies in India underlined that neither the fertilizers nor the organic sources in isolation can achieve sustainable production.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term application of organic manures alone in the form of well-rotten and good quality farmyard manure (FYM) has been reported to make nutrients available gradually, in synchrony with plant needs. Besides improving the physico-chemical properties of soil, the application of organic manures can also increase However, the inclusion of legumes, especially forage legumes, as a break crop during the third or fourth cycle can benefit RWS without impairing the food security [14]. Besides providing the green fodder for cattle, there is evidence that a forage legume crop can fix kg N ha −1 in the current season with a carryover effect ranging between 35-60 kg N ha −1 for the succeeding crop [16,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies carried out in Thailand (Kasem, draft PhD dissertation) and elsewhere (Jitsanguan, 2001; IFAD, 2002; IFAD, 2005; Giovannucci, 2007) have revealed that small farmers could benefit more from the production of vegetables and other produce that made use of organic fertilizers and bio‐pesticides, provided marketing opportunities are available. Regarding crop diversification, its role in efficient use of plant nutrients available in the soil has also been confirmed (Blade and Slinkard, 2002; Singh et al , 2002; Kar et al , 2003). Moreover, it could also contribute to employment generation, especially for the poor people in areas where non‐farming employment opportunities are scarce, and to their food security (Rasul and Thapa, 2003).…”
Section: Analytical Frameworkmentioning
confidence: 95%